2009
DOI: 10.1080/02841850802570561
|View full text |Cite
|
Sign up to set email alerts
|

Organ doses and effective doses in pediatric radiography: Patient-dose survey in finland

Abstract: In chest and sinus examinations, the amount of data was extensive, allowing national pediatric diagnostic reference levels to be defined. Parameter selection in pediatric examination protocols should be harmonized in order to reduce patient doses and improve optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 6 publications
4
17
2
Order By: Relevance
“…The effective doses are about the same as for adults because although the radiation dose per unit of radiopharmaceutical is greater in children than adults, a much smaller amount of a radiopharmaceutical is used for children. For additional information about the effective dose from various medical procedures, please see Huda and Vance (2007), ICRP (2008), Johnson and Birky (2012), Kiljunen et al (2009), Mettler et al (2008, and Yakoumakis et al (2007).…”
Section: Effective Dosementioning
confidence: 99%
“…The effective doses are about the same as for adults because although the radiation dose per unit of radiopharmaceutical is greater in children than adults, a much smaller amount of a radiopharmaceutical is used for children. For additional information about the effective dose from various medical procedures, please see Huda and Vance (2007), ICRP (2008), Johnson and Birky (2012), Kiljunen et al (2009), Mettler et al (2008, and Yakoumakis et al (2007).…”
Section: Effective Dosementioning
confidence: 99%
“…A number of studies have reported radiation dose measurements from some X-ray examinations; however, their results were only limited to the presentation of entrance surface dose (ESD) or dose-area product (DAP) measurements or the effective dose (E) for some age groups (Huda, 2002;Hart and Wall, 2004;Hart et al, 2009;Kiljunen et al, 2009;Olowookere et al, 2011). Nevertheless, the use of the effective dose to state the stochastic harm to patients from ionizing radiation is sometimes criticized (Valentin, 2007;McCollough et al, 2010;Pradhan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First, mean ± SD effective radiation dose in this pediatric cohort undergoing videourodynamics was 0.07 ± 0.05 mSv. This dose is comparable to that from a single x-ray of the kidneys, ureters and bladder in a 5-year-old child, 10 and less than that from a voiding cystourethrogram study across all age groups. 11,12 By comparison, the reported ED from a voiding cystourethrogram is 0.11 to 0.47 mSv in male newborns and 0.12 to 0.42 mSv in female newborns, and 0.28 to 0.93 mSv in 10-year-old males and 0.55 to 0.82 mSv in 10-year-old females.…”
Section: Discussionmentioning
confidence: 61%